Optimal Factor Taxation under Wage Bargaining - A Dynamic Perspective - Erkki Koskela; Leopold von Thadden (Center for Economic Studies and ifo Institute (CESifo), 2003)
We consider the issue of steady-state optimal factor taxation in a Ramsey-type dynamic general equilibrium setting with two distinct distortions: i) taxes on capital and labour are the only available tax instruments for raising revenues, and ii) labour markets are subject to a static inefficiency resulting from wage bargaining. If considered in isolation, under broad assumptions the two distortions create conflicting demands on the wage tax, while calling for a zero capital tax. By combining the two distortions, we arrive at the conclusion that both instruments should be used, implying that the zero-capital tax result in general is no longer valid under imperfectly competitive labour markets.
Keywords: 330; optimal taxation; imperfectly competitive labour markets; capital accumulation